The Role of Prenatal Environmental Risk Factors in Autism Spectrum Disorder Severity: Insight from Lead Exposure, Tobacco Smoke, and Low Birth Weight - Iskandar Iskandar; Yosef Dwi Cahyadi Salan; Adelia Anggraini Utama; Niarsari Anugrahing Putri; Gusti Muhammad Perdana Putera; Hapsari Lintang Sekartaji; Nisa Nur Agistni Eriana; Eko Suhartono (Gema Lingkungan Kesehatan, 2026)
Autism Spectrum Disorder (ASD) is a complex neurodevelopmental condition influenced by interactions between genetic susceptibility and environmental exposures during critical developmental periods. However, evidence regarding how environmental factors relate to ASD severity remains limited. This study aimed to examine the associations between urinary lead (Pb) levels, prenatal cigarette smoke exposure, history of low birth weight (LBW), and ASD severity, providing insights into potential environmental influences on clinical outcomes. A cross-sectional study was conducted among 43 children diagnosed with ASD attending a special needs school (SLB C) in Banjarbaru, South Kalimantan, Indonesia. Urinary Pb concentrations were measured using UV-Visible spectrophotometry. Information on prenatal cigarette smoke exposure and birth history was obtained through structured parental interviews. ASD severity was assessed using the Childhood Autism Rating Scale, Second Edition (CARS-2), and classified as mild–moderate or severe. Higher urinary Pb levels, prenatal cigarette smoke exposure, and a history of LBW were significantly associated with ASD severity, highlighting potential environmental risk factors that may influence clinical presentation and management strategies. In conclusion, among children with ASD in this school-based population, environmental and perinatal factors were associated with differences in ASD severity. While these findings are promising, emphasizing the need for further research can foster a sense of hope and motivation among researchers, clinicians, and students. Due to the cross-sectional design, causal inferences cannot be drawn. Further studies using longitudinal designs and objective exposure measurements are warranted.